A rare case of multiple pituitary adenomas in an adolescent Cushing disease presenting as a vertebral compression fracture - Ji-Yeon Song; Sue-Jean Mun; Soon-Ki Sung; Jae-Yeon Hwang; Seung-Kug Baik; Jee Yeon Kim; Chong-Kun Cheon; Su-Young Kim; Yoo-Mi Kim (Korean Society of Pediatric Endocrinology, 2017)
Cushing disease in children and adolescents, especially with multiple pituitary adenomas (MPAs), is very rare. We report 17-year-old boy with MPAs. He presented with a vertebral compression fracture, weight gain, short stature, headache, and hypertension. On magnetic resonance imaging (MRI), only a left pituitary microadenoma was found. After surgery, transient clinical improvement was observed but headache and hypertension were observed again after 3 months later. Follow-up MRI showed a newly developed right pituitary microadenoma 6 months after the surgery. The need for careful clinical and radiographic follow-up should be emphasized in the search for potential MPAs in patients with persistent Cushing disease.